STUDI PEMBUATAN PERMEN KURMA (Phoenix dactylifera L.) DENGAN PENAMBAHAN EKSTRAK LEMON (Citrus limon) - Jiniatunnissa BR Sitepu; Zulkifli Lubis (Agrintech: Jurnal Teknologi Pangan dan Hasil Pertanian, 2019)
Candy is a food that is liked much by children and adults. Now, there are many sweets that are circulating in the society namely Jelly candies. However, most of the sweets in the market are only concerned with the taste and appearance without the importance of health, so it needs to be developed that sweets can be good for the body, for example by using palm fruit and lemon extract. This research aims to find out how to manufacture date candies with basic materials of dates and lemons and know the comparison of the sweetness and acidity that much liked panelist. The study used the complete random draft (RAL) method with two factorial. Factor I is the amount of date fruit meat (K) consisting of 4 treatments, namely K1 = 30 g, K2 = 25 g, K3 = 20 g, K4 = 15 g. Factor II is the amount of lemon extract (L) consisting of 4 treatments, namely L1 = 20 ml, L2 = 15 ml, L3 = 10 ml , L4 = 5 ml. The observed parameters are moisture content, ash content, reduction sugar test, Sakarosa test, organoleptic taste test and organoleptic test texture. From the results of static analysis of each parameter: The amount of date fruit meat gives a different effect very real (p<0,01) against water content test, ash content, sugar reduction and Sakarosa while the lemon extract provides a different effect is very noticeable (p<0,01) against water content test, sugar reduction, organoleptic flavor and organoleptic texture.